REVIEW OF ANJANA (CORRYLIUM) PROCEDURE AND ITS PROBABLE MODE OF ACTION - Gamage Surangi, *Kankanan; Fiaz, Shamsa; Kumar, Sahoo Prasanta (International Journal of Ayurveda and Pharma Research, 2016)
Shalakya Tantra is one of the eight specialties of Ashtanga Ayurveda which deals with diseases occur above the clavicle specially related to the sensory organs. Eyes hold special status among all the sense organs because good vision is crucial for social and intellectual development of human beings. Hence authentic classics prescribed several preventive and curative measures for the management of ophthalmic disorders. Among them, topical treatments are very unique, effective in the management of eye diseases and are called â€œNetra Kriyakalpaâ€. Netra Kriyakalpa have very fast action on the target tissues of eye. Anjana is a medicinal preparation which is applied on the lower palpebral conjunctiva or the cul-de-sac. Its active principles may be transferred to the interior of the eye according to their hydrophilicity and lipophilicity mainly through the conjunctiva and cornea by paracellular and transcelullar pathways respectively. pH, viscosity, tonicity, molecular size and molecular weight of the active ingredients are highly responsible for the absorption of Anjana. According to its form Anjana is of 3 types i.e. Gutika, Rasakriya and Churna. Gutika and Churna types of Anjana can be correlated with ophthalmic suspensions and Rasakriya type is with aqueous solutions/eye drops. Gutika and Curna Anjana have micro particles which may be deposited in the cul-de-sas and thereby increase the bioavailability to enhance ocular absorption. Anjana therapy may be highly beneficial in the anterior segment disorders because of the presence of several anatomical, biological and physiological ocular barriers. However it gives better results on the posterior segment disorders also.